Guidelines for an alternative transit switch design. - Davis, David; United States. Federal Transit Administration; Transit Cooperative Research Program; National Research Council (U.S.). Transportation Research Board (Washington, D.C. Transportation Research Board, 2005)
This digest summarizes the results of TCRP Project D-7/Task 5, 'Transit Switch Design Evaluation.' The design guidelines described in this digest build on technical analyses conducted and published in TCRP Report 71, Volume 2: Transit Switch Design Analysis (Phase I). The digest was prepared by the Transportation Technology Center, Inc. (TTCI) in Pueblo, Colorado. David Davis served as principal author.
Caption title.
Sponsored by the Federal Transit Administration.
December 2005.
Includes bibliographical references.
Keywords: Electric railroads -- Switches; Railroad switches